Use of gemcitabine–platinum in Indian patients with advanced gall bladder cancer. (April 2015) - Sirohi, Bhawna; Rastogi, Sameer; Singh, Ashish; Sheth, Vipul; Dawood, Shaheenah; Talole, Sanjay; Ramadwar, Mukta; Kulkarni, Suyash; Shrikhande, Shailesh V
ABSTRACT : Background: Gemcitabine–platinum (Gem-P) is the current standard for patients with advanced gall bladder cancer.Materials & methods: This is retrospective analysis of a prospectively maintained database of 210 patients with advanced gall bladder cancer treated with Gem-P between January 2012 and September 2013.Results: Median age was 53 years, 65.2% females. In total, 158 patients had metastatic and 52 had locoregional disease. Median number of cycles was 5 (1–12). At a median follow-up of 10 months, median overall survival/progression-free survival was 10/5 months, respectively. On multivariate analysis, patients who underwent prior surgery for primary and locoregional disease had a significantly better progression-free survival and those with locoregional disease had a significantly better overall survival. A total of 45.7% received second-line chemotherapy.Conclusion: Use of Gem-P in Indian patients leads to slightly worse outcomes suggesting an aggressive biology.